2008
DOI: 10.1889/1.3069537
|View full text |Cite
|
Sign up to set email alerts
|

14.5: Invited Paper: Novel, Flexible AC Electroluminescent Lamps for Innovative Display Applications

Abstract: Novel, flexible ACEL lamps have been developed for innovative display applications. These lamps contain a single emissive layer comprising of ACEL phosphor, a binder, ferroelectric nanoparticles and optional dye. This architecture reduces fabrication costs and enables high luminances (ca. 200 cd/m2) to be achieved at 110 V and 400 Hz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…However, in principle, a thick-film AC-EL emissive system does need only one single layer, provided the total dielectric properties are still tolerable [63]. To this end, suitable binders need to incorporate the dielectric function, and phosphor particles need to be as small as possible.…”
Section: Materials For Ac-electroluminescencementioning
confidence: 99%
“…However, in principle, a thick-film AC-EL emissive system does need only one single layer, provided the total dielectric properties are still tolerable [63]. To this end, suitable binders need to incorporate the dielectric function, and phosphor particles need to be as small as possible.…”
Section: Materials For Ac-electroluminescencementioning
confidence: 99%
“…Thus the panels are operating well below the maximum potential if all the crystals were aligned with the field. As such panels commonly have high luminances (ca 200 cd/m 2 ) at 110 V and 400 Hz [2][3][4], then if crystal alignment was achieved one could expect luminances of almost 400 cd/m 2 without other factors that may also increase performance such as highly reflecting back electrodes. We have previously found that using reflective back electrodes with single binder layers between the electrodes it is possible to achieve 320 cd/m 2 .…”
Section: 6l / J Silver Late-news Papermentioning
confidence: 99%
“….It is now possible to fabricate such panels with only one layer between the electrodes making the panels highly flexible, in such devices the layer contains a binder the ACEL phosphor powder particles and the dielectric particles [3]. Modern uses of this technology include large area flexible ACEL panels for innovative display applications [4]. Using technology we have developed and reported previously it is possible to fabricate panels that have high luminances (ca 200 cd/m 2 ) at 110 V and 400 Hz [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aluminium on PET has recently been identified as a low cost replacement for printed silver back-electrodes in AC electroluminescent displays (ACEL) which have a number of niche applications, such as back-lights for instruments in cars, aeroplanes, mobile phones, illuminated displays for advertising and safety lights [11]. Their advantages are that they provide a distributed, uniform light sources, they can be made very thin (o 60 mm) and thus flexible and robust.…”
Section: Introductionmentioning
confidence: 99%